Growth, economic structure and informality - Juan Chacaltana; Florence Bonnet; Juan Manuel Garcia (International Labour Organization (ILO), 2022)
This paper explores the relationship between economic growth and informality and highlights the role of GDP growth and its composition in the level and evolution of informality, using country data from 1991 to 2019. The analysis reveals a weak relationship, although with important differences across regions and income levels. Coefficients are higher in middle-income countries. This means that the same growth rate generates different impacts on informality depending on the country, probably due to pre-existing levels of informality, the economic structure or institutional and other variables. Economic structure appears to be the key determinant of informality, even after controlling for endogeneity, using different proxies of informality or including institutional variables. These results confirm that the economic structure and pattern of growth matters for formalization. This calls for policies that promote changes in the productive structure, including a broader, more diversified base and more economic complexity and technological sophistication, to ensure inclusive growth.
Keywords: 330; employment; informal employment; economic conditions; economic growth; jobless growth; informal economy; economic sectors; industrial restructuring